On the accuracy of an emitter localization method based on multipath exploitation in realistic scenarios - Al Imran, M. A.; Ank, E.; Dalveren, Y.; Tabakcioglu, M. B.; Kara, A. (Taylor & Francis Ltd, 2022)
This study aims to evaluate the accuracy of a method proposed for passive localization of radar emitters around irregular terrains with a single receiver in Electronic Support Measures systems. Previously, the authors targeted only the theoretical development of the localization method. In fact, this could be a serious concern in practice since there is no evidence regarding its accuracy under the real data gathered from realistic scenarios. Therefore, an accurate ray-tracing algorithm is adapted to enable the implementation of the method in practice. Then, realistic scenarios are determined based on the geographic information system map generated to collect high-resolution digital terrain elevation data, as well as realistic localization problems for radar emitters. Next, simulations are performed to test the localization method. Thus, the performance of the method is verified for practical implementation in the electronic warfare context for the first time. Lastly, the performance bounds of the method are discussed.
Keywords: Digital terrain elevation data; geographic information system; localization; multipath; radar; ray-tracing